Growth analysis of the everbearing strawberry ‘Delizzimo’ under controlled temperature and photoperiod conditions - R. Rivero; A. Sønsteby; O. M. Heide; K. A. Solhaug; S. F. Remberg (CABI Agriculture and Bioscience)
Abstract Background There is limited information on the effect of environment on vegetative growth in everbearing (EB) strawberry (Fragaria x ananassa Duch.) and its comparison with the situation in seasonal flowering types. Methods We investigated the effects of photoperiod (daylengths of 10 and 20 h) and temperature (12, 19 and 26 ℃) on leaf growth, dry matter production and partitioning, concentrations of soluble sugars, starch, and chlorophyll in the F1 hybrid ‘Delizzimo’ grown in a single experiment in daylight phytotron compartments in Norway. Results Plants grown in the long photoperiod (LD) and higher temperatures had greater leaf growth and higher dry matter production than those under short day (SD) and low temperature conditions. Growth decreased over the 39 days of the experiment. The changes in growth in the different environments were associated with changes in relative growth rate (RGR) and these were driven by changes in net assimilation rate (NAR) and leaf area ratio (LAR). The plants directed more dry matter to the leaves and crowns under LD and high temperature conditions and less dry matter to the roots, thus increasing the plant’s shoot to root ratio. Long days decreased the concentrations of sugars and starch in most of the tissues, while the effect of temperature was more complex. Higher temperatures increased the concentrations of sugars in the leaves in LD, while starch accumulated in the roots under SD and low temperature conditions. Sucrose accumulated temporarily in the crowns at the time of flower bud formation in LD and higher temperatures. Conclusions The results of the experiment demonstrate that the effects of photoperiod and temperature on the vegetative growth of everbearing strawberry are similar to those reported for seasonal-flowering strawberry. Increases in temperature and photoperiod and the resulting enhancement of the RGR was associated with accumulation of soluble sugars (sucrose, glucose and fructose) in the above-ground parts of the plant, whereas low temperature and SD resulted in accumulation of starch in the roots.